Far-infrared/THz photodetector with self-assembled Quantum dots - Nam, H.; Song, J.; Choi, W.; Lee, J.; Yang, H.; Zhang, B.; Lu, W. (International Topical Meeting on Microwave Photonics, MWP 2005, 2005)
In this paper, we report 21 μm photoresponse with InAs/InGaAs/GaAs quantum-dot-in-a-well photodetector structure. The self-assembled InAs quantum dots were grown on InGaAs/GaAs well structure via atomic layer molecular beam epitaxy and fabricated as intersubbamd photoconductlve structure. The far-infrared/THz 21 μm photoresponse was measured at 4.2K. Photoresponses were observed over the range of λ = 3 μm to 25μm with peaks at 21, 15, 8 μm, respectively.